Needed adaptations in psychological treatments for people with vision impairment: A Delphi study, including clients, relatives, and professionals - Braakman, Jessica; Sterkenburg, Paula Sophia (Frontiers in Psychology, 2023)
Objective: This study aimed to identify the themes that should be addressed in adapting mental health treatments. Method: A Delphi study was conducted among 37 experts: professionals, persons with a visual impairment, and relatives of clients with a visual impairment. Results: The Delphi-consultation identified seven categories (factors) that were deemed important in the treatment of mental health problems for clients with a visual impairment: visual impairment, environment, stress, emotions, professional, treatment-setting and material. Factors regarding clients’ visual impairment such as severity of the impairment influence the extent to which adjustments are needed in treatment. The professional considered the most important factor in the treatment. For example, the professional is a explicator for what the clients visually misses out on. Conclusion: The specific visual impairment of the client required individual adaptations in the psychological treatment.